Risk factors for infection with human immmunodeficiency virus among European expatriates in Africa. Issue 6648 (3rd September 1988) - Bonneux, L.; Van der Stuyft, P.; Taelman, H.; Cornet, P.; Goilav, C.; van der Groen, G.; Piot, P.
Abstract : The pattern of cases of AIDS in Belgium suggests that Europeans infected with human immunodeficiency virus (HIV) acquired the infection in Africa. The prevalence of infection was assessed in Belgian advisers and European expatriates and risk factors for infection defined in a case-control study of expatriate men. Fifteen (1.1%) of 1401 Belgian advisers working in Africa and 41 (0.9%) of 4564 European expatriates living in Africa, were positive for antibody to HIV in a voluntary screening programme in Belgium. Among subjects with antibody to HIV the ratio of men to women was 3:1. These subjects did not have a history of intravenous drug abuse or blood transfusion and only one was homosexual. In a case-control study of 33 expatriate men who had antibody to HIV and 119 controls the men with antibody reported significantly more female sexual partners, who were more commonly local; and significantly more sexual contact with prostitutes in Africa. They had a significantly higher prevalence of history of sexually transmitted disease and had received significantly more injections by unqualified staff in Africa during the previous five years. No specific sexual practices were associated with having antibody to HIV. After multivariate analysis sexual contact with local women (adjusted odds ratio 14.7; 95% confidence interval 2.81 to 76.9), sexual contact with prostitutes (adjusted odds ratio 10.8 (1.6 to 71.9), and injections by unqualified staff (adjusted odds ratio 13.5 (3.7 to 49.8) remained independent risk factors for infection. European expatriates in Africa were at increased risk from infection with HIV and were a means of introducing HIV into the heterosexual population in Europe. Transmission from women to men by vaginal intercourse seemed to be the most probable route of infection.